2009
DOI: 10.1136/jech.2008.082123
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the relationship of long working hours with health status and health-related behaviours

Abstract: The association of overtime with different health indicators among men could be explained by their role as the family breadwinner: in situations of family financial stress men work overtime in order to increase the income and/or accept poor working conditions for fear of job loss, one of them being long working hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
138
3
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(151 citation statements)
references
References 44 publications
7
138
3
3
Order By: Relevance
“…The detrimental impact of extreme overtime work has often been demonstrated, but the unfavorable impact of moderately long working hours on health and well-being has not been consistently shown (1)(2)(3)(4)(5)(6). Moderately long working hours and their impact on health have been related to family financial stress and the breadwinner role: in situations of family financial stress, breadwinners are likely to be forced to work long hours in order to increase the family income (7,8). Therefore, apart from methodological reasons, the contradictory results of previous studies could be explained by different breadwinner models across countries.…”
contrasting
confidence: 44%
See 2 more Smart Citations
“…The detrimental impact of extreme overtime work has often been demonstrated, but the unfavorable impact of moderately long working hours on health and well-being has not been consistently shown (1)(2)(3)(4)(5)(6). Moderately long working hours and their impact on health have been related to family financial stress and the breadwinner role: in situations of family financial stress, breadwinners are likely to be forced to work long hours in order to increase the family income (7,8). Therefore, apart from methodological reasons, the contradictory results of previous studies could be explained by different breadwinner models across countries.…”
contrasting
confidence: 44%
“…Some studies have highlighted the crucial role of choice in determining a person's response, in terms of health and well-being, to working long hours (7)(8)(9)(10)(11)(12)(13). Two theoretical approaches have been proposed to account for the obligation to work long hours: consumerism and bargaining power (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Data from more than Japanese 50,000 workers from 4 companies were evaluated. The results showing an inverse association between overtime work and prevalence of hypertension contradicted two former studies (Artazcoz et al, 2009;Yang et al, 2006), but confirmed others (Wada et al, 2006;Nakanishi et al, 2001). Despite the large database, the authors highlighted the cross-sectional design as the main study limitation that left the possibility open of residual effects of potential confounders and differences in assessments of overtime and blood pressure evaluation among the companies.…”
Section: Health and Working Timecontrasting
confidence: 53%
“…Long working hours increase the risk of various health problems, such as coronary heart diseases, work-related injuries, sleep disorders, and mental disorders (1)(2)(3). Work schedules can affect the length and quality of sleep, leading to low productivity and workplace hazards.…”
mentioning
confidence: 99%